A new control-oriented transient model of variable geometry turbocharger. (15th April 2017) - Bahiuddin, Irfan; Mazlan, Saiful Amri; Imaduddin, Fitrian; Ubaidillah,
Abstract: The flow input of a variable geometry turbocharger turbine is highly unsteady due to rapid and periodic pressure dynamics in engine combustion chambers. Several VGT control methods have been developed to recover more energy from the highly pulsating exhaust gas flow. To develop a control system for the highly pulsating flow condition, an accurate and valid unsteady model is required. This study focuses on the derivation of governing the unsteady control-oriented model (COM) for a turbine of an actively controlled turbocharger (ACT). The COM has the capability to predict the turbocharger behaviour regarding the instantaneous turbine actual and isentropic powers in different effective throat areas. The COM is a modified version of a conventional mean value model (MVM) with an additional feature to calculate the turbine angular velocity and torque for determining the actual power. The simulation results were further compared with experimental data in two general scenarios. The first scenario was simulations on fixed geometry positions. The second simulation scenario considered the nozzle movement after receiving a signal from the controller in different cases. The comparison between simulation and experimental results showed similarities in the recovered power behaviours the turbine inlet area increases or vice versa. The model also has proved its reliability to replicate general behaviour as in the example of ACT cases presented in this paper. However, the model is incapable to replicate the detailed and complicated phenomena, such as choking effect and hysteresis effect. Highlights: A control-oriented model of a variable geometry turbocharger turbine is proposed. Isentropic and actual power behaviour estimations on turbocharger turbine. A simulation tool for developing active control systems of turbocharger turbines.